Predictors in mortality risk stratification in patients with chronic kidney disease on hemodialysis - Escalona González, Sergio Orlando; González Milán , Zoraida Caridad; Rodríguez Espinoza , Katiuska Danay; Molina Vega, Raymar (Revista Cubana de Nefrología, 2025)
Introduction: The identification of predictors of mortality in patients with chronic kidney disease on hemodialysis, which allows the identification of early treatment to patients at higher risk of death, it is necessary in practice current clinic. Objective: To describe the predictors of mortality in patients with disease chronic kidney on hemodialysis. Methods: A bibliographic review of the theoretical foundations on the Mortality risk stratification in patients with chronic kidney disease on hemodialysis. The resources available through Infomed (PubMed, PubMed Central, SciELO, Web of Science, Scopus, Ebsco, Clinical Key), as well as Google Scholar. The search strategies were: “chronic kidney disease OR renal insufficiency OR end-stage renal disease and hemodialysis and mortality and predictors OR predictive models”. Development: Chronic kidney disease mortality risk stratification in hemodialysis is complex, taking into account that there are numerous traits that can influence the outcome end of patients. Multiple variables have an implication in the classification of the risk of the patient, which depend on the history, the clinical evolution of the disease, paraclinical results and adherence to hemodialysis. Conclusions: The predictors in the risk stratification of Mortality in patients with chronic kidney disease on hemodialysis. These Predictors do not act in isolation, but rather interact with each other to influence the patient prognosis. The comprehensive and systematic evaluation, which integrates these variables can help personalize treatment and improve clinical outcomes.